Collective action, property rights, and devolution of natural resource management: exchange of knowledge and implications for policy - Katon, Brenda; Knox, Anna; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2001)
Policies to devolve responsibility for natural resource management to local bodies have become widespread in the past 20 years. Although the theoretical advantages of user management have been convincing and the impetus for devolution policies strong, the actual outcomes of devolution programs in various sectors and countries have been mixed. This paper summarizes key research findings on factors that contribute to effective devolution programs in the forestry, fisheries, irrigation, and rangelands sectors, which were presented and discussed at an international Policy Workshop on Property Rights, Collective Action and Devolution of Natural Resource Management, June 21-25, 1999, in Puerto Azul, the Philippines.